ANALISIS KEKASARAN PERMUKAAN PADA PROSES CNC TURNING MATERIAL BAJA ST 42 MENGGUNAKAN METODE TAGUCHI - HERMANSYAH RHOMADAN; Robert Napitupulu; Husman Husman (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Minimum surface roughness is the target to be achieved in the workpiece machining process using CNC Turning. Where the smaller the surface roughness value will result in a better (smaller-is-better) surface roughness. This research aimsTo determine the variable combination settings (feeding motion, spindle rotation and infeed depth) to the minimum surface roughness, and to determine the percentage contribution of parameters that affect surface roughness in the CNC Turning process. The research method used the Taguchi method with L9 orthogonal matrix experimental design (33), because there are three process parameters that have three levels. Repetition is done twice. From the research results, the surface roughness value is obtained. In addition, the levels obtained from the spindle rotation process parameters (Rpm), feeding motion (feeding), and the depth of feeding that can minimize surface roughness. The results of this study indicate the right combination setting of parameter variables to produce the minimum surface roughness is a spindle rotation of 1250 put / min, infeed depth of 0.5 mm, feeding motion of 1.0 mm / rev. The percentage contribution of parameters that affects surface roughness is the infeed depth of 24.41%.